On securing a common monetary policy in Europe - R.I. MCKINNON (PSL Quarterly Review, 2013)
The work looks at the EEC’s integration, and specifically the evolution from a pseudo exchange-rate union to full monetary integration and the technical actions of coordinating the actions of national central banks. First the monetary impact of international payments imbalances is assessed. The discount mechanism and partial sterilisation is then considered. Finally, the author looks at restricting the scope of open-market operations.